生态文明建设 ：上海强制性垃圾分类政策 = Ecological civilisation : A study of Shanghai’s mandatory waste sorting policy - 洪巧玲 Ang, Keow Leng (Nanyang Technological University, 2020)
本文将以上海的强制性垃圾分类政策作为论文的中心。 随着中国经济迅速增长，它的垃圾产量也随之而升。面对严峻的垃圾管理形势，中国正在向垃圾宣战2019年7月，上海市正式启动《上海市生活垃圾管理条例》，对城市生活垃圾的分类投放与监管进行了较为细致的管理。因此，笔者将以此为视角，探索中国环境保护策略从改革开放以来经历了什么变化，以及中国垃圾管理系统所面临的挑战。分析中国之前的垃圾分类运动为何会屡次失败的原因，以此推测上海垃圾分类政策未来的走向和所面临的挑战。 This paper will focus on Shanghai’s newly implemented Mandatory Waste Sorting Policy. With the rapid growth of China's economy, its waste volume also rises. In the face of a severe situation of waste management, China is officially declaring “war on the issue of domestic waste.” In July 2019, Shanghai officially launched the "Shanghai Household Waste Management Regulation ", which imposes a mandatory waste sorting regulation on all household waste. Therefore, from this perspective, the author will explore what changes have taken place in China's environmental protection strategy since the “reform and opening-up”, as well as the challenges faced by China's domestic waste management system. This paper also analyses the reasons why China’s waste sorting movement has failed repeatedly in the past, and speculates the future trend and challenges of the new Shanghai garbage classification policy.